AKTIVITAS SENYAWA BIOAKTIF DARI EKSTRAK ETIL ASETAT DAUN YAKON (Smallanthus sonchifolius) SEBAGAI PENGHAMBAT ENZIM α-GLUKOSIDASE - Riska Diana; Lilik Sulastri; Partomuan Simanjuntak (PROSIDING SEMINAR KIMIA, 2023)
Yakon (Smallanthus Sonchifolius) leaves in Indonesia, better known as insulin leaves, scientifically have various properties and one of them is antidiabetic. This study aims to determine the activity of secondary metabolites contained in the ethyl acetate extract of yakon (Smallanthus Sonchifolius) leaf as an inhibitor of the -glucosidase enzyme. Yakon leaf ethyl acetate extract using eluent from TLC results. Until several sub-factions are obtained. These sub-fractions were combined in TLC and tested for activity. The sub-fraction with the best activity in Back column chromatography and TLC and tested until the IC50 value is obtained. The results showed that the ethyl acetate extract of yakon leaves had inhibitory activity of the -glucosidase enzyme with an IC50 of 45,67 ppm. The results of column chromatography separation showed that sub-fraction 6.5 was a sub-fraction with an IC50 value of 42,23 ppm. Conclusion: Yakon leaf ethyl acetate extract had better activity than purified F6.5 and acarbose as a positive control with an IC50 value of 21,36 ppm. Keywords : Smallanthus sonchifolius, α -glucosidase inhibitory enzyme, IC50, Indonesian medicinal plant